Active site engineering of single-atom carbonaceous electrocatalysts for the oxygen reduction reaction - Chen, Guangbo; Zhong, Haixia; Feng, Xinliang (Chemical Science, 2021)
The electrocatalytic oxygen reduction reaction (ORR) is the vital process at the cathode of next-generation electrochemical storage and conversion technologies, such as metal-air batteries and fuel cells. Single-metal-atom and nitrogen co-doped carbonaceous electrocatalysts (M-N-C) have emerged as attractive alternatives to noble-metal platinum for catalyzing the kinetically sluggish ORR due to their high electrical conductivity, large surface area, and structural tunability at the atomic level, however, their application is limited by the low intrinsic activity of the metal-nitrogen coordination sites (M-Nx) and inferior site density. In this Perspective, we summarize the recent progress and milestones relating to the active site engineering of single atom carbonous electrocatalysts for enhancing the ORR activity. Particular emphasis is placed on the emerging strategies for regulating the electronic structure of the single metal site and populating the site density. In addition, challenges and perspectives are provided regarding the future development of single atom carbonous electrocatalysts for the ORR and their utilization in practical use.
CRIS-Team Scopus Importer:2023-03-20